Middle Triassic trachytic lava flows associated with coeval dyke swarm in the North Patagonian Massif: A postorogenic magmatism related to extensional collapse of the Gondwanide orogen - González, Santiago Nicolás (2017)
The Marifil Volcanic Complex is an extended volcanic and pyroclastic unit outcropping in the North Patagonia. It has been included in the Chon Aike large igneous province associated to the thermal anomaly of the Karoo plume. The Marifil Volcanic Complex is mainly composed of rhyolites, dacites, rhyodacites and minor trachytes and trachyandesites. The latter are common in the base of the unit. The upper acidic rocks have been dated between 192 Ma to 151 Ma (Early to Middle Jurassic) by K-Ar, Ar-Ar and Rb-Sr methods. On the other hand, the age of the mesosilicic rocks range from 221 Ma to 173 Ma (K-Ar whole rock ages).In this research, we revise the stratigraphic relations, geochemistry and petrography of the mesosilisic rocks from Marifil Volcanic Complex. Aditionally, a new U-Pb crystallization age of 247.22 ± 0.46 Ma was obtained for an trachytic lava flow that covers Permian granitoids and which is covered by rhyolitic ignimbrites. The mentioned mesosilisic rocks are chemically trachytes and trachyandesites and show subduction margin affinities. In the area, a Triassic trachyandesitic dyke swarm has been considered as an expression of Gondwanide postorogenic extension in the North Patagonian Massif.Basis on our new age data and considering the compositional and stratigraphic differences we separate the Triassic trachytic to trachyandesitic rocks from the Jurassic rhyolites and dacites. These two groups of rocks represent different geotectonic events in the Southwestern margin of Pangea.